(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In this scientific article, methods of surgical treatment of actinomycosis in cattle in the conditions of the Republic of Karakalpakstan and their effectiveness are studied. Actinomycosis is a chronic inflammatory infectious disease caused by the Actinomyces bovis bacterium, manifested mainly in the lower jaw, tongue, and neck areas in the form of granulomatosis. This disease, which has a negative effect on the health of farm animals, if not detected in time, leads to the death of the animal and causes huge economic losses for farms.